Identification of the distribution pattern of macroalgae caulerpa racemosa in Ternate City - Rovina Andriani; Muhammad Djanib Achmad; Najamuddin Najamuddin; Syahnul Sardi Titaheluw (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Coastal ecosystems in Ternate have high biodiversity, including the macroalga Caulerpa racemosa, which contributes to ecosystem stabilization and mitigation of ocean acidification. However, environmental degradation due to human activities poses a serious threat, so analyzing the distribution and density of macroalgae is important for sustainable ecosystem management. This study aimed to analyze the distribution pattern and density of C. racemosa in Kastela and Gamalama waters, Ternate City. Data collection was conducted from May to August 2024 using the line transect method with 1x1 m quadrants in two research locations. Each site had three 50 m long transect lines with five quadrants per transect. Density was calculated based on the number of individuals per unit area, while distribution patterns were analyzed using the Morisita index (Id). Environmental data such as temperature, salinity and pH were also measured to understand the factors affecting macroalgae distribution. Spatial analysis using GIS software visualized distribution patterns. Results showed that C. racemosa had a concentrated distribution pattern (Id 1) in both study sites, with higher average densities in Kastela waters than Gamalama. Environmental factors, including temperature and substrate type, significantly influenced the distribution of this species. This study provides important data to support ecosystem-based management and sustainable coastal conservation, and fills an information gap on the impacts of ecological pressures on macroalgae in this region.Keywords:Caulerpa racemosaTernateDistributionCoastal Ecosystem